2018
DOI: 10.1186/s40248-018-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory failure as presentation of late-onset Pompe disease complicating the diagnostic process as a labyrinth: a case report

Abstract: BackgroundAcute respiratory failure can be triggered by several causes, either of pulmonary or extra-pulmonary origin. Pompe disease, or type II glycogen storage disease, is a serious and often fatal disorder, due to a pathological accumulation of glycogen caused by a defective activiy of acid α-glucosidase (acid maltase), a lysosomal enzyme involved in glycogen degradation. The prevalence of the disease is estimated between 1 in 40,000 to 1 in 300,000 subjects.Case presentationThis case report describes a dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In our study, both of the two patients found to have LOPD has displayed respiratory and neurologic symptoms for more than 1 year, but they were detected only during an episode of acute respiratory failure with the need of RHDCU admission. This latency of the diagnosis may seem too high, but it is much less than other literature reports [8, 16, 17]. In line with our results, Kishnani et al [19] recently reported that patients with early respiratory involvement can be diagnosed sooner than those presenting with only muscular symptoms and/or hyperCPKaemia.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, both of the two patients found to have LOPD has displayed respiratory and neurologic symptoms for more than 1 year, but they were detected only during an episode of acute respiratory failure with the need of RHDCU admission. This latency of the diagnosis may seem too high, but it is much less than other literature reports [8, 16, 17]. In line with our results, Kishnani et al [19] recently reported that patients with early respiratory involvement can be diagnosed sooner than those presenting with only muscular symptoms and/or hyperCPKaemia.…”
Section: Discussionsupporting
confidence: 84%
“…Acute respiratory failure requiring mechanical ventilation in Intensive Care Units (ICU) or in Respiratory High Dependency Care Units (RHDCU) may be the first clinical presentation of the disease [7]. However, LOPD with a prevalent respiratory derangement is not easily and promptly identified during an acute respiratory failure episode because the critical illness itself doesn’t allow a clearly diagnostic electromyographic study [8].…”
Section: Introductionmentioning
confidence: 99%
“…This revealed the two pathogenic variants already described. One variant results in a premature codon and due to nonsense mediated decay results in haploinsufficiency [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. This variant has been reported repeatedly in the literature with Pompe's patients including LOPD.…”
Section: Discussionmentioning
confidence: 99%
“…Recessive mutations in this gene are linked to congenital myasthenic syndrome (CMS17), a severe neuromuscular disorder associated to respiratory failure [ 43 ]. Respiratory related symptoms (dyspnoea on effort, reduced physical capacity and recurrent infections) and respiratory failure are often evident in the later stages of LOPD [ 45 ]. The two rare and deleterious LRP4 variants identified only in this patient alter the highly conserved residues laying in important domains of the protein ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%